PELATIHAN PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS SOCIOSCIENTIFIC ISSUE SEBAGAI IMPLEMENTASI KURIKULUM MERDEKA BAGI MGMP IPA KABUPATEN MUSI RAWAS - Muhamad Yusup (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2024)
Using socioscientific issues (SSI) can make learning science more relevant to student life. The problem identified is still the lack of the ability of science teachers in Musi Rawas district to develop defense devices. The training aimed to improve science teacher skills to develop learning devices based on SSI in the JHS based on the Merdeka Curriculum. At the in-service training activity, participants study and discuss the material presented by the trainer. During the job training, participants undertake independent learning activities to develop the SSI-based science teaching module following the tasks assigned to the service training activity. The results showed an improvement in the participants' SSI understanding of SSI, accompanied by an increased awareness of how to associate SSI with science learning. An increase in participants' understanding of how to identify and choose relevant SSI to be taught in the classroom and how to facilitate the discussion of SSI that encourages critical thinking and moral reflection. In addition, there has been an increase in the confidence to be able to guide students in the analysis of information and various perspectives as well as to make decisions related to SSI.